Studies on Working Qualities of Indian Timbers-V - Rawat, B. S.; Pant, B. C. (Indian Forester, 1980)
The Present paper is in continuation of the earlier ones (2,3,5&6) on the subject, in which working qualities of 29 Indian Species have already been reported, under four wood working operations. Following the same procedure. Working qualities of ten more species namely Anogeissus latifolia H.P.), Anogeissus latifolia (A P.) Cedrus deodara, Chloroxylon swietenia, Dysoxylum malabaricum, Gmelina arborea, Grewia tiliifolia, Melia dubia. Pterocarpus marsupium and Xylia xylocarpa have been reported in this paper. The working quality index and ease of working for each or the species, have also been calculated and given for overall comparison of the species under study.